Estimasi Kualitas Karkas Hidup pada Kerbau Rawa dan Kerbau Sungai dengan Ultrasonografi pada Berbagai Umur - Veni RVS; Isdoni Isdoni; Agung S. P. Lumban Tobing; Mokhamad Fakhrul Ulum (Fakultas Peternakan Universitas Halu Oleo, 2024)
Ultrasonography is a non-invasive diagnostic tool which potential for examining carcasses periodically, cheap, easy, and accurate to demonstrate carcass characteristics, quantity and quality of meat. This study aims to predict the quality of live carcass in swamp buffaloes and river buffaloes based on age and breed by ultrasonography. Ultrasound imaging was carried out with a longitudinal and transverse point of view using a convex transducer with a frequency of 5 MHz and a depth of 180 mm. There were 10 swamp buffaloes and 10 river buffaloes that were grouped into 1-3 years (n = 5) and 3-6 years (n = 5). The result of ultrasound images appears as anechoic images of muscle and hyperechoic images of fat and bone. Carcass analysis used AUSMEAT with the regression y = 0.4546+0.1697 x with R2 of 0.9833 for marbling score and the regression y = - 0.03003+0.4217 x with R2 of 0.9933 for percentage of intramuscular fat showed that swamp buffaloes and river buffaloes aged 3-6 years had the Longissimus dorsi muscle thickness, rump muscle thickness, backfat thickness, rump fat thickness, marbling score and percentage of intramuscular fat were higher than aged 1-3 years (P<0.05). However, analysis of ultrasound images based on breed showed that swamp buffaloes and river buffaloes had the same carcass quality (P>0.05).